Atmospheric bromoform at Mace Head, Ireland: seasonality and evidence for a peatland source - L. J. Carpenter; D. J. Wevill; S. O'Doherty; G. Spain; P. G. Simmonds (Atmospheric Chemistry and Physics, 2005)
In situ atmospheric observations of bromoform (CHBr3) made over a 2.5 year period at Mace Head, Ireland from May 2001- Dec 2003, including during the NAMBLEX (North Atlantic Marine Boundary Layer Experiment) campaign, show broad maxima from spring until autumn and winter minima, with mixing ratios of 5.3+1.0 pptv (mid March - mid October) and 1.8+0.8 pptv (December-February). This indicates that, unlike CHCl3, which has a summer minimum and winter maximum at Mace Head, local biological sources of CHBr3 have a greater influence on the atmospheric data than photochemical decay during long-range transport. The emission sources are predominantly macroalgal, but we find evidence for a small terrestrial flux from peatland ecosystems, which so far has not been accounted for in the CHBr3 budget. Sharp increases in CHCl3 and CHBr3 concentrations and decreases in O3 concentrations occurred at night when the wind direction switched from an ocean- to a land-based sector (land breeze) and the wind speed dropped to below 5 ms-1. These observations infer a shallow atmospheric boundary layer with increased O3 deposition and concentration of local emissions of both CHCl3 and CHBr3. The ratio of ΔCHCl3/ΔCHBr3 varied strongly according to the prevailing wind direction; from 0.60+0.15 in south-easterly (100-170° and northerly (340-20°) air to 2.5+0.4 in north-easterly (40-70°) air. Of these land-sectors, the south-easterly air masses are likely to be strongly influenced by macroalgal beds along the coast and the emission ratios probably reflect those from seaweeds in addition to land sources. The north-easterly airmasses however had an immediate fetch inland, which locally is comprised of coastal peatland ecosystems (peat bogs and coastal conifer plantations), previously identified as being strong sources of atmospheric CHCl3 under these conditions. Although we cannot entirely rule out other local land or coastal sources, our observations also suggest peatland ecosystem emissions of CHBr3. We use correlations between CHCl3 and CHBr3 during the north-easterly land breeze events in conjunction with previous estimates of local wetland CHCl3 release to tentatively deduce a global wetland CHBr3 source of 20.4(0.4-948) Gg yr-1, which is approximately 7% of the total global source.